Kesalahan Bahasa pada Buku Ajar Bahasa Arab Kelas IX MTs Semester Genap yang Disusun Oleh MGMP Kabupaten Kediri - Afandi, Moh. Yusuf; Sa’idah, Ratna (Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah, IAIN Kediri, 2023)
In the world of education, there is a textbook, which is a book that is used to clarify and simplify the presentation of material so that students are more active in learning and independent towards the expected knowledge or skills. Textbooks must have good quality so that learning objectives can be achieved properly. In the Minister of Education and Culture of the Republic of Indonesia Number 8 of 2016 Article 3 Paragraph 5 states that the contents of a textbook in a textbook must fulfill several aspects, namely material aspects, linguistic aspects, presentation aspects, and graphical aspects. The focus of this research lies in the linguistic aspect. In reality, there are still textbooks that do not meet the aspects of using language that is good and right, especially in learning Arabic. This study aims to find out the language errors contained in arabic textbooks class IX Islamic Junior High School even semester compiled by Deliberations of Subject Teachers in Kediri district, and correction of the language errors. This study used the library method using content analysis techniques, in which researchers analyzed textbooks and studied various reference books to obtain a theoretical basis for the problem under study. The results of the research show that there are several language errors in the arabic textbooks. These errors are reviewed from three sides, namely from the side of syntax, morphology, and writing. Syntactic errors consist of eight forms of errors. As for morphological errors, there are six forms of errors. Then for writing errors there are four forms of errors.